KONTRIBUSI DPD ASITA (ASOSIASI PERUSAHAAN PARIWISATA INDONESIA) SULAWESI SELATAN DALAM MENINGKATKAN DAYA SAING BIRO PERJALANAN DAN KUNJUNGAN WISATAWAN - Nur Azizah Muhiddin; Anda Prasetyo Anda Prasetyo; Renold Renold (Politeknik Pariwisata Makassar, 2025)
The impact of the covid19 pandemic is still being felt today, especially in the tourism sector, this can be seen in the data on tourist visits in South Sulawesi. The purpose of this study is to examine the efforts of ASITA in increasing tourist visits in South Sulawesi, both domestic and foreign and to analyse the obstacles faced by ASITA in its efforts to increase tourist visits to South Sulawesi. This research uses a qualitative approach that describes the data that has been obtained in the form of writing. The results of the study of ASITA's efforts in increasing the number of tourist visits are: (1) emphasising the diversification of tourism promotion targets, (2) promotion in more specific markets, (3) encouraging people to use official agents when on holiday, (4) It is hoped that the Makassar City government can actively participate in supporting policies aimed at improving the tourism industry. The obstacles that ASITA faces in its efforts to increase tourist visits to South Sulawesi are: (1) budget efficiency, which affects promotional activities, (2) infrastructure damage, which hinders tourist travel. To overcome these problems, a more focused and collaborative approach is needed. One of the strategic steps to reduce dependence on the MICE sector sourced from the government, budget efficiency that is less targeted and inadequate road infrastructure need to be addressed immediately as the local economy is highly dependent on tourism